Assessing the main characteristics of sheep and goat milk production value chains at farmer level: Opportunities and constraints - Tzouramani I.; Hadjipavlou G.; Sossidou E.; Ligda C. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
In the frame of the DoMEsTIc project (EU FP7 ARIMNet), one of the main objectives was to undertake an in-depth assessment of the information related with the utilized marketing channels for local sheep and goat milk and milk products. The identified livestock distribution channels are influenced by particular interrelated factors. Such factors are linked with the production and profit orientation (i.e. sales price, quantity of milk, income), production cost and product differentiation, loyalty, speed of payment, personal relationships, isolation of the farm and determine the profile of small ruminant farmers and their marketing strategies. Using the framework of the value chain, this study identified the different actors, assessed the governance mechanisms in the value chain, analysed the opportunities for upgrading within the chain and revealed the constraints that prevent the development of the sheep and goat milk value chain with special focus on the farmers’ point of view. In this paper, results from two case studies from Greece and Cyprus are presented. Data were collected by semi-structured personal interviews with farmers. All types of the supply chain were identified in the survey. The main characteristics of these supply chains revealed both common and diverse issues relating to the two case studies. Finally, this study will try to offer applied insights on ways to improve and propose alternative policies and optimal interventions in the value chain of local sheep and goat breeds to safeguard the livestock farmers.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)